Common and Specific Genetic Risk Factors for Three Disorders with Depressive Symptoms - Rafikova, E. I.; Shibalev, D. V.; Shadrina, M. I.; Slominsky, P. A.; Guekht, A. B.; Ryskov, A. P.; Vasilyev, V. A. (Russian journal of genetics, 2022)
Searching for genetic causes of depressive and anxiety disorders has been going on for about three decades. However, the accumulated experimental data do not allow us to come to a final conclusion about the influence of certain genes on the risk of the disease and the severity of its course. Most studies of candidate genes were carried out using samples of patients with different nosological forms of depression. The aim of our work was to check whether the previously found associations are common for all depressive spectrum disorders or there are loci that specifically affect the risk of developing a certain disease. The study involved patients with disorders characterized by severe depressive symptoms ( n = 357). Patients were divided into three samples according to the diagnosis: depressive episode (DE), recurrent depression (RD), and mixed anxiety and depressive disorder (MADD). The polymorphic locus 40 bp VNTR of gene SLC6A3 was associated with all studied disorders; the LL genotype was less common in patients and was associated with a low risk of disease. The polymorphism 120 bp VNTR in gene DRD4 was associated with RD and MADD. The rs6311 locus of gene HTR2A was associated with DE and MADD. A specific genetic risk factor for RD in the studied samples was the rs53576 polymorphism of gene OXTR . The genotype homozygous for the minor allele (AA) was associated with a low risk of RD. None of the studied polymorphic loci influenced the severity of depression symptoms. The loci rs6311 of gene HTR2A and 120 bp VNTR of gene DRD4 were associated with symptoms of situational and personality anxiety. The severity of situational anxiety symptoms was also influenced by the loci rs53576 of gene OXTR and 16–17 bp VNTR of gene SLC6A4 .